2008
DOI: 10.1111/j.1751-553x.2007.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal septic arthritis as the initial presentation of multiple myeloma

Abstract: Septic arthritis induced by Streptococcus pneumoniae is an uncommon manifestation of pneumococcal infection. Pneumococcus has been identified as the inciting pathogen in only 6% of cases of septic arthritis in recent retrospective studies (Ross et al., 2003). Approximately 50% of patients with pneumococcal septic arthritis have a preceding or concurrent extra-articular focus of infection. The septic joint evolves from hematogenous seeding of the highly vascular synovial membrane by bacteria. Polyarticular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Complex systemic pneumococcal infection with polyarticular manifestation14 occurs very rarely. There is rising evidence for the perceived frequency of S pneumoniae as a cause for septic arthritis over the last few decades 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex systemic pneumococcal infection with polyarticular manifestation14 occurs very rarely. There is rising evidence for the perceived frequency of S pneumoniae as a cause for septic arthritis over the last few decades 10.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal septic polyarthritis is an infrequently reported septic manifestation due to pneumococcal pneumonia 14. It has been shown that only 1.3% of pneumococcal bacteraemias lead to a manifestation in the ankles 5.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory infections with group A hemolytic streptococci have the potential to cause arthritis in immunocompromised conditions. [ 29 ] Infections following bleeding from abrasions at the joint site also carry the risk of further infection of the joint fluid by bacteria coming into contact with the wound site, leading to arthritis. Endogenous bacterial infections mainly include blood‐borne bacteria, medical infections and septic lesions near joints.…”
Section: Introductionmentioning
confidence: 99%
“…The tumourous products, either abnormal immunoglobulins or inflammatory cytokines, may bring about such deleterious effects as renal failure, hyperviscosity syndrome and lytic bone lesions. Increased susceptibility to certain infections is another common manifestation in these patients 14. Occasionally, the disease presents with an extramedullary mass consisting of abnormal plasma-cell nests 5.…”
Section: Introductionmentioning
confidence: 99%